Brill's Companion to Theocritus - Sistakou, Evina; Rengakos, Antonios; Kyriakou, Poulheria (Brill's Companions to Classical Studies., 2021)
Through the variety of its scholarly perspectives, Brill Companion to Theocritus offers a tool for the study of one of antiquity's foremost poets. Offering a thorough examination of textual transmission, ancient commentaries, literary dialect, and poetic forms, the present volume considers Theocritus' work from novel theoretical perspectives, such as gender and emotions. It expands the usual field of inquiry to include religion, and the poet's reception in Late Antiquity and early modern times. The various chapters promote Theocritus' profile as an erudite poet, who both responds to and inaugurates a rich and variegated tradition. The combination of these various perspectives places Theocritus at the crossroads of Ptolemaic patronage, contemporary society, and art.